Formulation and Evaluation of Hydrogel Preparations from Jeneponto Horse Oil (Equus caballus) - Siti Saharah Abdullah; A. Asmawati Saad; Taufiq Dalming; Dwi Resky Lestari (Lembaga Pengembangan Kinerja Dosen, 2025)
Horse oil, traditionally used as a medicinal remedy, contains essential amino acids that contribute to the repair of bones, muscle tissues, and skin, particularly in wound healing. Hydrogel preparations serve as topical wound dressings that provide a cooling effect, reduce inflammation, and support faster wound recovery. The aim of this research was to develop and evaluate the stability of a hydrogel formulated with horse oil (Equus caballus). The study involved heating horse fat at 105°C for two hours using an oven, followed by formulating the extracted oil into a hydrogel with a sodium carboxymethyl cellulose (NaCMC) base. The preparation underwent several tests including organoleptic, homogeneity, pH, spreadability, adhesion, viscosity, and stability evaluations. Results showed that formulations F1, F2, and F3 satisfied all evaluation criteria and maintained stability without changes in physical characteristics or pH levels.